PERSEPSI GURU DAN SISWA TENTANG SCIENTIFIC APPROACH DALAM PEMBELAJARAN IPA - Purbosari, Rheinanda Arum; Erman, Erman (Universitas Negeri Surabaya, 2024)
This study aimed to determine the perceptions of teachers and students about the Scientific Approach in science learning. This study used a survey method, with the subjects of 2 science teachers and 10 random students from grades VII and VIII who used the inquiry-based scientific approach. The research instruments used, namely learning documents, teacher and student interviews, teacher and student questionnaire sheets, and 10 questions about understanding the scientific approach. The data collection techniques used in this research are document analysis, interviews, questionnaires, and comprehension questions which will later be described. The results of analyzing learning documents and interviews stated that the teacher had compiled complete learning documentation and in accordance with the stages of the Scientific Approach. The implementation of the stages of Scientific Approach by teachers and students obtained from questionnaire analysis stated that learning using Scientific Approach was carried out appropriately, but at the stage of communicating did not go well due to time constraints. The results of the test stated that the quality of student learning using inquiry-based Scientific Approach learning was quite good.